Simulation of impurity transport in the peripheral plasma due to the emission of dust in long pulse discharges on the Large Helical Device - M. Shoji; G. Kawamura; R. Smirnov; A. Pigarov; Y. Tanaka; S. Masuzaki; Y. Uesugi (Nuclear Materials and Energy, 2017)
Two different plasma termination processes by dust emission were observed in long pulse discharges in the Large Helical Device. One is a plasma termination caused by large amounts of carbon dust released from a lower divertor region. The other is termination caused by stainless steel (iron) dust emission from the surface of a helical coil can. The effect of the dust emission on the sustainment of the long pulse discharges are investigated using a three-dimensional edge plasma transport code (EMC3-EIRENE) coupled with a dust transport code (DUSTT). The simulation shows that the plasma is more influenced by the iron dust emission from the helical coil can than by the carbon dust emission from the divertor region. The simulation revealed that the plasma flow in divertor legs is quite effective for preventing dust from terminating the long pulse discharges. Keywords: Dust, EMC3-EIRENE, DUSTT, Long pulse discharge